New n-nonadecanoyl-β-sitosterol and other constituents from the stem-bark of Anacardium occidentale. Issue 8 (3rd April 2021) - Shehu, Abdullahi; Ponnapalli, Mangala Gowri; Mahboob, M.; Prabhakar, P. V.; Olatunji, Gabriel Ademola
Abstract: A new steroidal ester bearing n -nonadecanoyl moiety (1 ) and a mixture of isomeric cerebrosides (2 ) along with two known compounds were isolated from the methanol extract of the stem-bark of Anacardium occidentale . The structure of the new steroidal ester was determined as 3- n -nonadecanoyl-β-sitosterol on the basis of modern spectroscopic techniques (IR, ESI-MS, HR-ESIMS, 1D and 2D NMR) and chemical degradation studies. The structures of the known compounds were identified as gallic acid and tanacetene by comparison of the spectroscopic data with those of reported data. The mixture of cerebrosides was confirmed based on the analysis of 1D and 2D NMR. These compounds were evaluated for cytotoxicity against human cancer cell lines A549, SCOV3 and rat normal cell line NRK49f. Abstract :